Association of Hepcidin with Hepatitis C induced Diabetes Mellitus - Hina Arif ,Umbreen Ahmed ,Shahid Ahmed , Komal Nadeem (Journal of Rawalpindi Medical College, 2017)
To compare serum hepcidin levels of patients with hepatitis C induced diabetes mellitus with healthy controls Methods: Sixty individuals were included in the study. Thirty were diagnosed cases of chronic hepatitis C who developed diabetes mellitus during the course of HCV infection. Thirty age and gender matched healthy controls were included. Individuals with acute hepatitis C, familial diabetes mellitus, iron deficiency anemia, recent history of blood transfusion, iron or erythropoietin supplementation and inflammatory diseases like rheumatoid arthritis, renal, cardiac, pulmonary diseases and on interferon therapy were excluded from the study. Blood samples were collected from all the individuals and serum hepcidin levels were measured by ELISA. Results: Significant decrease in serum hepcidin levels was found in patients with the chronic hepatitis C and diabetes mellitus having mean value of 2.7±1.03ng/ml as compared with controls having mean value of 28.5±5.3ng/ml. The difference among the two groups was significant at p-value of <0.001. Conclusion: Serum hepcidin levels in patients with chronic hepatitis C with diabetes mellitus are significantly less as compared to healthy controls.